Intuitive eating and the female athlete triad in collegiate runners - Thomson, J.; Almstedt, H. C. (Nutrients, 2025)
Background: Female collegiate runners may be at high risk for disordered eating and poor bone health, which are characteristics of the female athlete triad. Intuitive eating can promote healthy eating behavior and adequate calorie intake, central variables in calculating energy availability, an underlying cause of low bone mass in athletes. Poor bone health can contribute to injury, preventing optimal performance for athletes. The purpose of this study was to assess intuitive eating, energy availability, and bone mineral density in female college runners with comparison to non-athletes. Methods: Female college athletes (n = 13, 19.5 ± 1.4 yrs) and non-athletes (n = 12, 19.9 ± 1.3 yrs) completed the Intuitive Eating Scale, Eating Disorder Examination Questionnaire, and menstrual history survey. Bone mineral density and body composition were measured using a dual-energy X-ray absorptiometer (DEXA). A 3-day diet record and exercise log were used to assess dietary intake, estimate energy expenditure, and calculate energy availability. Results: Intuitive eating was inversely correlated with disordered eating (r = -0.596, p = 0.002). Intuitive eating scores were not correlated to calorie intake, energy availability, bone mass, or percent body fat. Runners consumed significantly more calories, calcium, magnesium, phosphorus, and protein (g/kg) than non-athletes. Energy availability and bone mineral density were not significantly different between runners and non-athletes. Conclusions: Intuitive eating is associated with healthy eating behaviors in college-age females and was not related to energy availability, bone density, or body composition in this population. Future research could explore the use of intuitive eating principles in reducing disordered eating and addressing low energy availability in female runners and non-athletes.